Evaluation of a new double‐lumen endobronchial tube with an integrated camera (VivaSight‐DL™): a prospective multicentre observational study. (1st April 2015) - Koopman, E. M.; Barak, M.; Weber, E.; Valk, M. J. A.; de Schepper, R. T. I.; Bouwman, R. A.; Huitink, J. M.
Summary The VivaSight‐DL™ is a new single‐use double‐lumen endobronchial tube with an integrated camera. We studied this device in 151 consecutive patients scheduled for elective thoracic surgery in four different hospitals. Endobronchial intubation was successful in 148 patients (98%) (95% CI 94–99%). Median (IQR [range]) endobronchial intubation time was 59 (47–82 [17–932]) s and lung isolation was successfully achieved in 147 (99%) patients (95% CI 96–99%). A fibreoptic bronchoscope was required to assist endobronchial tube placement in 19 (13%) patients (95% CI 8–19%). Sore throat was reported by 37 (25%) patients (95% CI 18–33%), but no major complications were observed. We have reported the successful use of the VivaSight double‐lumen tube for endobronchial intubation in a multicentre observational trial.